2020
DOI: 10.1038/s41598-020-57629-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pregabalin for the treatment of chronic pruritus of unknown origin, assessed based on electric current perception threshold

Abstract: Chronic pruritus of unknown origin (CPUO) is defined as itching lasting more than 6 weeks in the absence of discernible skin lesions. Pregabalin is used to treat patients with CPUO. In this study, we aimed to investigate differences in the perception threshold of itch sensation between patients with CPUO and healthy individuals and to evaluate the efficacy of pregabalin for CPUO. At baseline, week 2, and week 4 after treatment initiation, the visual analogue scale (VAS) score was measured to assess pruritus se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This coincided with the study of sensitive skin by Polena et al 10 . Moreover, the same results have been found between patients with chronic itch compared with healthy controls 24–26 . However, several studies have shown controversial results 7–9 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This coincided with the study of sensitive skin by Polena et al 10 . Moreover, the same results have been found between patients with chronic itch compared with healthy controls 24–26 . However, several studies have shown controversial results 7–9 .…”
Section: Discussionsupporting
confidence: 85%
“…This coincided with the study of sensitive skin by Polena et al 10 Moreover, the same results have been found between patients with chronic itch compared with healthy controls. [24][25][26] However, several studies have shown controversial results. [7][8][9] Despite the small sample size in one of these studies, 8 the mean value reported by Ham et al 7 and Sun et al 9 showed small differences with large variances in the study groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that nervous system activity may play an important role in the mechanism of UP. Lee et al showed that Pregabalin (75 mg twice daily) reduced chronic pruritus 5 . Despite the evidence of efficacy Pregabalin in UP, 6–8 it was found that only 4% UP patients have been used Pregabalin 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al showed that Pregabalin (75 mg twice daily) reduced chronic pruritus. 5 Despite the evidence of efficacy Pregabalin in UP, [6][7][8] it was found that only 4% UP patients have been used Pregabalin. 4 This low statistic can be due to the fear of drugs side effects and uncertainty of the effective dose with minimal side effects in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…An open-label study of 22 patients found a daily dose of pregabalin 150 mg led to a significant decrease in itch after 4 weeks of treatment32. Another study on the efficacy of pregabalin in CPUO found that pruritus was improved in 7 of 10 patients, and corresponded to a decrease in C -fiber nerve sensitivity to electrical stimulation33. A case series found treating CPUO patients with gabapentin 300 mg/d with the daily incremental increase to 1800 mg/d during the next few weeks led to the excellent response and complete control of itch within a month31,34.…”
Section: Systemic Treatmentsmentioning
confidence: 99%